A Novel Recyclable Ni/Cu/Fe Termetallic Nanocatalyst for the Synthesis of Propargylamines through the A3‐Coupling Reactions. Issue 1 (2nd January 2020) - Daryanavard, Marzieh; Ataei, Ali; Sheykhabadi, Parvan Ghaderi; Rafiee, Ezzat; Joshaghani, Mohammad
Abstract: A novel Ni/Cu/Fe nanocatalyst was prepared via a three‐step procedure for the A 3 ‐coupling reaction of an aldehyde, an amine, and a terminal alkyne to synthesize the corresponding propargylamine. Oleic acid was used in the second step to avoid aggregation of CuFe2 O4 nanoparticles. The prepared NiO/OA‐CuFe2 O4 (Ni/Cu/Fe) was characterized using X‐ray diffraction (XRD), scanning electron microscopy/wavelength dispersive X‐ray (SEM/WDX), particle size analyzer, fourier transform infrared (FT‐IR) and atomic absorption spectroscopy (AAS). A variety of propargylamines was synthesized using a very small amount of this efficient and inexpensive nanocatalyst in toluene as the solvent at 100 °C. Due to high magnetic properties of the prepared catalyst, its isolation and recycle were very easy, and it was used in five repetitive cycles. Abstract : A new recyclable Ni/Cu/Fe nanocatalyst has been prepared via a three‐step procedure and fully characterized. This nanocatalyst exhibits an outstanding catalytic activity towards an inexpensive and economical protocol for A 3 ‐coupling reaction of the aldehydes, amines, and terminal alkynes to synthesis the corresponding propargylamines.